Effect of cow manure concentration for biomethane production in batch fermentation - Min Athaha, Qatrun Nadia (2015)
Biomethane is a valuable gaseous compound that is chemically similar with natural gas. Thus, it can be used for the same application as in natural gas, for example; electricity generation, water heating, space heating, cooking as well as fuel for vehicles. This study was carried out to evaluate the effect of different concentration of cow manure for biomethane production in batch fermentation. The sample used in this study were a mixture of cow manure and food waste at different concentration with adjusted initial pH 7. The sample consist of 10% cow manure, 20% cow manure, 30% cow manure, 40% cow manure, 50% cow manure, 100% cow manure and 100% food waste. All the samples were fermented in batch fermentation at 37oC for three weeks. The gas produced was collected and measured in daily basis. The gas collected was analysed using gas chromatography to determine the concentration of biomethane in the sample. From the result obtained, the concentration of biomethane was observed to be highest (36.9%) at 100% cow manure sample.